2008
DOI: 10.1016/j.hrthm.2008.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the molecular phenotype of two arrhythmogenic right ventricular cardiomyopathy (ARVC)-related plakophilin-2 (PKP2) mutations

Abstract: BACKGROUND-Arrhythmogenic right ventricular cardiomyopathy (ARVC), has been linked to mutations in desmosomal proteins, including plakophilin2 (PKP2). Little is known about the changes in cellular function and structure that follow expression of ARVC-relevant PKP2 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…Together, these results suggest that the p.Arg79X mutation leads to a loss of myocardial integrity characteristic of ARVC/D. 28 Finally, Asimaki et al showed that immunohistochemical analysis of conventional endomyocardial biopsy samples appears to be both a highly sensitive and specific diagnostic test for ARVC/D, as was demonstrated in a group of 11 ARVC/D patients. 26 Reduced immunoreactive signal levels of plakoglobin and Cx43 were found to be a consistent feature in patients with ARVC/D.…”
Section: B Amentioning
confidence: 85%
See 1 more Smart Citation
“…Together, these results suggest that the p.Arg79X mutation leads to a loss of myocardial integrity characteristic of ARVC/D. 28 Finally, Asimaki et al showed that immunohistochemical analysis of conventional endomyocardial biopsy samples appears to be both a highly sensitive and specific diagnostic test for ARVC/D, as was demonstrated in a group of 11 ARVC/D patients. 26 Reduced immunoreactive signal levels of plakoglobin and Cx43 were found to be a consistent feature in patients with ARVC/D.…”
Section: B Amentioning
confidence: 85%
“…For the p.Arg79X mutation in PKP2, however, the consequences of the expression of the mutation have been studied, using neonatal rat ventricular myocytes. 28 This showed that the mutant protein failed to localise to the cell membrane, in contrast to endogenous PKP2 and DSP. The major cardiac gap junction protein connexin-43 (Cx43) was also reduced in this model.…”
Section: B Amentioning
confidence: 98%
“…4,14 Moreover, expression levels of other desmosomal proteins, in particular plakoglobin, have been suggested to be reduced in ARVC-related cardiac tissue. [14][15][16] In addition, cellular expression of 2 PKP2 nonsense mutations has produced unstable PKP2 proteins; 17,18 however, the process of protein degradation remains unclear. To date there are limited data about molecular and genetic mechanisms of missense mutations in the C-terminal armadillo domains, as well as their consequences in the context of human cardiac disease.…”
mentioning
confidence: 99%
“…In the latter it is necessary for heart formation and for the onset and coordination of rhythmic heart beat, 18,[44][45][46][47][48] be it directly or indirectly (for further involvements of sodium channels or gap junctions, see also recent knockdown experiments). [49][50][51][52] Most impressive in the discussions about possible functional roles of Pkp2 are certainly the recent reports that cardiac Pkp2 is by far the most sensitive protein, which in mutated forms can contribute to arrhythmogenic ventricular cardiomyopathies (ARVCs). [46][47][48][49][50][51][52][53] Moreover, in Pkp2 gene knockdown experiments, it has also been shown that its stabilizing effect on cell-cell adhesion in rat cardiomyocyte cultures is so important that a reduction in Pkp2 can result in a complete separation of the two junctional membranes.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] Moreover, in Pkp2 gene knockdown experiments, it has also been shown that its stabilizing effect on cell-cell adhesion in rat cardiomyocyte cultures is so important that a reduction in Pkp2 can result in a complete separation of the two junctional membranes. [49][50][51][52] Thus, in myxoma tumors growing in a very viscous, mucoid-gelatinous matrix, the acquisition of Pkp2 to the adherens junctions may have an important stabilizing effect and strengthen cell-cell adhesions, in particular those connecting the long and thin cell processes.…”
Section: Discussionmentioning
confidence: 99%